The own-voice benefit for word recognition in early bilinguals - Cheung, Sarah; Babel, Molly (Frontiers in Psychology, 2022)
The current study examines the self-voice benefit in an early bilingual population. Female Cantonese-English bilinguals produced words containing Cantonese contrasts. A subset of these minimal pairs was selected as stimuli for a perception task. Speakers’ productions were grouped according to how acoustically contrastive their pronunciation of each minimal pair was and these groupings were used to design personalized experiments for each participant, featuring their own voice and the voices of others’ similarly-contrastive tokens. The perception task was a two-alternative forced-choice word identification paradigm in which participants heard isolated Cantonese words, which had undergone synthesis to mask the original talker identity. Listeners were more accurate in recognizing minimal pairs produced in their own (disguised) voice than recognizing the realizations of speakers who maintain similar degrees of phonetic contrast for the same minimal pairs. Generally, individuals with larger phonetic contrasts were also more accurate in word identification for self and other voices overall. These results provide evidence for an own-voice benefit for early bilinguals. These results suggest that the phonetic distributions that undergird phonological contrasts are heavily shaped by one’s own phonetic realizations.